Abitare 50 years of design : the best of architecture, interiors, fashion, travel, trends - Piazza, Mario (New York Rizzoli International Publications, 2010)
This text reproduces the best selected pages from the annals of Abitare magazine from 1961 to the present, with the stories published chronologically. Each story is presented in full, reflecting the original design and the milieu of the time.
Where, how, and with whom does Abitare live? The Abitare reader. Dwelling with readers 2000s -- Speaking of architecture, but not only architecture 1990s -- 1980s -- Abitare 1961-2011 1970s -- The culture of living 1960s -- The Italian "normal" An Italian feeling Piera Peroni -- Franca Santi Gualteri -- Paola Antonelli -- Italo Lupi -- Alessandro Mendini -- Stefano Boeri -- Mario Piazza --
Originally published in Italian as Abitare 50 anni di design in 2010 by RCS Libri S.p.A.
Text in English and Italian.
Keywords: Design -- History -- 20th century; Architecture, Modern -- History -- 20th century; Interior decoration -- History -- 20th century; Popular culture -- History -- 20th century -- Italy -- Periodicals; Italy -- Periodicals